Fructo-oligosaccharides and iron bioavailability in anaemic rats: the effects on iron species distribution, ferroportin-1 expression, crypt bifurcation and crypt cell proliferation in the caecum. Issue 8 (28th October 2014) - Lobo, Alexandre R.; Gaievski, Eduardo H. S.; De Carli, Eduardo; Alvares, Eliana P.; Colli, Célia
<x content-type="archive" xml:space="preserve">Abstract</x> The present study investigated the effects of fructo-oligosaccharides (FOS) on the bioavailability of Fe from ferric pyrophosphate (FP), a water-insoluble compound, in Fe-deficient anaemic rats that were subjected to a Hb repletion assay. Male Wistar rats (n 64) were fed adequate or low (8 mg/kg) Fe diets for 15 d followed by 1 or 2 weeks of Fe repletion with diets providing 35 mg Fe/kg as ferrous sulphate (FS), FP or FP that was mixed with 7·5 % FOS in the form of yacon flour or Raftilose P95 (RAF), a purified source of FOS. The effects of FOS were observed within the 1st week of the repletion period. Fe bioavailability was improved by FOS supplementation, as measured by Hb regeneration efficiency and hepatic Fe stores, which were more pronounced in the RAF group. Moreover, RAF supplementation resulted in a higher biological value relative to that of the FP group. FOS supplementation resulted in caecal enlargement, in addition to acidification and Fe species redistribution in the caecal contents relative to the control rats. These effects occurred concomitantly with decreased ferroportin (FPN)-1 expression in the caecal mucosa, which was similar in magnitude to that observed in the FS group. Caecum mucosal morphometry was influenced by FOS supplementation, whereas crypt fission and cell proliferation were highest in the caecum of the RAF group. These results reinforce the effects of FOS as Fe bioavailability enhancers in anaemic rats that are sustained by early changes in their caecal environment (decreased mucosal FPN-1 expression and increased Fe absorbability, crypt fission and cellularity).